PENGEMBANGAN BAHAN AJAR BERBASIS PEMECAHAN MASALAH PADA MATA KULIAH ALJABAR LINEAR - Lilis Marina Angraini; Astri Wahyuni (Universitas Swadaya Gunung Jati., 2021)
This research aims to produce teaching materials through the learning obstacle analysis of mathematics education students in mathematical problem solving ability in Linear Algebra Courses that are practically tested. This type of research is research and development. The subjects of this study were 40 students in the Mathematics Education Study Program at the Islamic University of Riau in the third semester of 2019/2020. In this study, the data used were the results of the validation questionnaire trial data that was assessed by experts called the validator. The data obtained will be analyzed using qualitative descriptive analysis. Based on the results of the study, the percentage of overall product trial results obtained was 91.86% with a very practical category. This means that the developed learning tool is very easy to use by students in the learning process and can also overcome student learning difficulties (learning obstacle) in this case the ability to solve mathematical problems in Linear Algebra. Overall the results of the study indicate that the learning tools developed are suitable for use and can improve student learning outcomes.